Analisis Pemasaran Pinang di Kecamatan Amarasi Selatan, Kabupaten Kupang - Maria I. N. Seran; Damianus Adar; Hans Luther Telnoni (Undana Press, 2019)
This research has been carried out in Sonraen and Nekmese Villages Amarasi Selatan Sub District, Kupang District in July to August, 2018. The objectives of this study were to (1) Know the areca nut marketing channels in South Amarasi Subdistrict, (2) Know the marketing margins areca nut in South Amarasi District, (3) Knowing the efficiency of marketing costs in the District of South Amarasi, and (4) Know the level of transmition elasticity of the price of areca nut in South Amarasi District. Sampling was done in stages, namely the first stage of determining the location by purposive sampling, namely Sonraen and Nekmese Villages. The second stage determining the sample farmer by using proportional random sampling. The total respondents were 75 people. Data collected primary data and secondary data. Primary data is obtained from the results of direct interviews with respondents, while secondary data is obtained from relevant agencies in this study. The data analysis tool used in this study consists of; 1) descriptive analysis, 2) margin marketing analysis 3) marketing cost efficiency analysis 4) analysis of price transmission elasticity. The results showed that, (1) There are two Marketing Channels of areca in South Amarasi Subdistrict. (2) Marketing Margin of Areca obtained in channel one amounting to Rp. 3000, and on channel two Rp. 4000 (3) Efficiency of areca nut marketing costs in get on channel one in the amount of 0.18%, while on channel two is 0.74%. (4) and the level of elasticity of the betel price transmission is 0.38 Penelitian ini telah dilakukan di Desa Sonraen dan Desa Nekmese Kecamatan Amarasi Selatan, Kabupaten Kupang pada bulan Juli sampai bulan Agustus Tahun 2018. Tujuan dari penelitian ini adalah untuk, (1) Mengetahui saluran pemasaran pinang di Kecamatan Amarasi Selatan, (2) Mengetahui marjin pemasaran pinang di Kecamatan Amarasi Selatan, (3) Mengetahui efesiensi biaya pemasaran di Kecamatan Amarasi Selatan, dan (4) Mengetahui tingkat elastisitas transmisi harga pinang di Kecamatan Amarasi Selatan. Pengambilan sampel dilakukan secara bertahap yaitu tahap pertama penentuan lokasi secara purposive sampling yaitu Desa Sonraen dan Desa Nekmese.Tahap kedua penentuan petani contoh dengan menggunakan proportional random sampling. Total responden sebanyak 75 orang. Data yang dikumpulkan beruapa data primer dan data sekunder.Data primer diperoleh dari hasil wawancara langsung dengan responden, sedangkan data sekunder diperoleh dari instansi yang terkait dalam penelitian ini. Alat analisis data yang dipakai dalam penelitian ini terdiri dari; 1) analisis deskriptif, 2) analisis marjin pemasaran 3) analisis efesiensi biaya pemasaran 4) analisis elastisitas transmisi harga. Hasil penelitian menunjukkan bahwa, (1) Saluran Pemasaran Pinang di Kecamatan Amarasi Selatan Ada Dua Saluran Pemasaran (2) Marjin Pemasaran Pinang yang di peroleh padasaluran satu sebesar Rp 3000, dan pada saluran dua sebesar Rp 4000 (3) Efesiensi biaya pemasaran pinang yang di peroleh pada saluran satu sebesar 0,18 %, sedangkan pada saluran dua sebesar 0,74%. (4) dan tingkat elastisitas transmisi harga pinang sebesar 0,38.